2021
DOI: 10.5098/hmt.17.12
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Liquid Air Jet Pump

Abstract: A jet pump or an ejector uses primary fluid flow as motive fluid to entrained secondary fluid. In this paper, the main intention is to find suction flow rate, primary flow rate, secondary flow rate, loss factors and ejector efficiency for an applied pressure. The values of the different loss factors estimated are primary nozzle loss factor (Kp)=0.06, suction loss factor (Ks)=0.04-0.1, mixing loss factor (Km)=0.07-0.1 and diffuser loss factor (Kd)=0.0289. It is found that with the increase in pressure across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…al.2016). However, the amount of heat flux has increased exponentially after the semiconductor revolution owing to the size reduction of the system V. (W. Bhatkar, et. al.…”
Section: Introductionmentioning
confidence: 99%
“…al.2016). However, the amount of heat flux has increased exponentially after the semiconductor revolution owing to the size reduction of the system V. (W. Bhatkar, et. al.…”
Section: Introductionmentioning
confidence: 99%
“…In most of heating, ventilating, air conditioning and refrigeration (HVACR) industries, R134a refrigerant is used which is having GWP of 1300 much more than ecological norms. Bhatkar et al ( , 2015Bhatkar et al ( , 2021 found that there is no ideal refrigerant for any specific application. While selecting the refrigerant, compromise between thermodynamic, chemical, physical, operating and environmental properties are to be considered.…”
Section: Introductionmentioning
confidence: 99%